2021
DOI: 10.1017/s0033291721002403
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of socioeconomic status in cognition of people with schizophrenia: results from a Latin American collaboration network with 1175 subjects

Abstract: Background Cognition heavily relies on social determinants and genetic background. Latin America comprises approximately 8% of the global population and faces unique challenges, many derived from specific demographic and socioeconomic variables, such as violence and inequality. While such factors have been described to influence mental health outcomes, no large-scale studies with Latin American population have been carried out. Therefore, we aim to describe the cognitive performance of a representative sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 66 publications
1
6
0
3
Order By: Relevance
“…A collaboration network in Latin American evaluated the socioeconomic status of 1175 participants, which uncovered that subjects with a lower income were more related to cognition decline. [21] In the present paper, we also found that in middle aged and older people, a lower income may lead to a decreased cognitive function. People with improved sleep duration may have a better cognitive function, [22] but a cohort study in the Doetinchem also revealed that middle-aged people who had too long sleep duration may also result in a lower cognitive function.…”
Section: Discussionsupporting
confidence: 71%
“…A collaboration network in Latin American evaluated the socioeconomic status of 1175 participants, which uncovered that subjects with a lower income were more related to cognition decline. [21] In the present paper, we also found that in middle aged and older people, a lower income may lead to a decreased cognitive function. People with improved sleep duration may have a better cognitive function, [22] but a cohort study in the Doetinchem also revealed that middle-aged people who had too long sleep duration may also result in a lower cognitive function.…”
Section: Discussionsupporting
confidence: 71%
“…Education, income, and occupational status are positively associated with disease identification and realistic estimates of lifetime prevalence of depression. Social status with higher education provides a modest protection against schizophrenia [14]. In addition, the SES factors of education, parental education, and income were more related to cognition in patients than in common people.…”
Section: The Protective Role Of Sesmentioning
confidence: 91%
“…A social desirability score was computed using the sum of the responses to three items (10, 16, 22) of the CTQ-SF minimization-denial subscale (Church et al, 2017). Given the extensive literature linking psychotic disorder to social and economic disadvantage and poor cognitive (Czepielewski et al, 2022; Husain et al, 2018) and psychosocial functioning (Izquierdo et al, 2021), parental SES (Hollingshead & Redlich, 2007) was also considered as a covariate.…”
Section: Methodsmentioning
confidence: 99%